Investigating Coxiella burnetii infection in a breeding cattery at the centre of a Q fever outbreak. Issue 12 (December 2013) - Kopecny, Lucy; Bosward, Katrina L; Shapiro, Amanda; Norris, Jacqueline M
The potential role of cats in transmitting Coxiella burnetii to humans was highlighted in a Q fever outbreak, linked to a caesarean section in a breeding queen, in an Australian small animal veterinary hospital. The objectives of this study were to evaluate the C burnetii seroreactivity of the breeding queen and other cats residing at the same breeding cattery (n = 27) and to evaluate C burnetii infection of the breeding queen by molecular and histological methods. Three assays [complement fixation test (CFT), indirect immunofluorescence assay (IFA) and enzyme-linked immunosorbent assay (ELISA)] were used for serological evaluation. Additionally, uterine and ovarian samples collected from the breeding queen 11 weeks post-parturition were assessed by routine and specialised histological methods and polymerase chain reaction. The breeding queen showed strong seropositivity using CFT (titre 1/32), IFA (titre phase I 1/8192 and phase II 1/8192) and ELISA; however, the reproductive tract showed no evidence of pathology or C burnetii infection. A number of cattery-confined cats were identified as seropositive to phase II and/or phase I C burnetii . Serological detection of C burnetii in a breeding cattery linked to a Q fever outbreak indicates likely infection by this bacterium in Australian feline populations, re-confirming the relevance of this zoonosis.